Management of knowledge workers - Hans K. Hvide; Eirik Gaard Kristiansen (Institute for the Study of Labor (IZA), 2012)
We study how firm-specific complementary assets and intellectual property rights affect the management of knowledge workers. The main results show when a firm will wish to sue workers that leave with innovative ideas, and the effects of complementary assets on wages and on worker initiative. We argue that firms protected weakly by complementary assets must sue leaving workers in order to obtain positive profits. Moreover, firms with more complementary assets pay higher wages and have lower turnover, but the higher pay has a detrimental effect on worker initiative. Finally, our analysis suggests that strengthening firms' property rights protection reduces turnover costs but weakens worker initiative.
Keywords: J30; J60; 330; entrepreneurship; innovation; intellectual property rights; litigation; personnel economics; R&D; start-ups; worker mobility; Hochqualifizierte Arbeitskräfte; Immaterialgüterrechte; Industrielle Forschung; Personalmanagement; Theorie